Impact of English Instruction at The Elementary Schools on The Students Achievement of English at The Lower Secondary School - Sri Rachmajanti (TEFLIN, 2008)
The current study is intended to examine the effect of time of learning, English teachers characteristics, teaching and learning process characteristics, socio-economic context and students characteristics in the teaching of English at the elementary schools on the students achievement of English at the first year of lower secondary school. Two kinds of research designs were implemented, an ex post facto and a tracer study. Therefore, the data were collected in two ways in order to (1) discover the students English achievement at the lower secondary school and (2) observe the prior English instruction at the elementary school. The study adopted the statistical analysis of multiple regressions. The subjects consisted of 172 students who obtained the English instruction at the third and fourth grades of the elementary school, 172 students parents, and 31 English teachers in the five (5) sub districts of Pemerintah Kota Malang. The students were to do the communicative English test and fill out two kinds of questionnaires; whereas, the teachers were interviewed. The students parents had also to fill out a questionnaire on their perception on the English instruction at the elementary school. The finding shows that there is an impact of the teaching English starting at the fourth grade of elementary school on the students achievement of English at the first year of lower secondary school